On Some Double Weighted Fractional Integral Inequalities - Bezziou, Mohamed; Dahmani, Zoubir; Khameli, Amina (Sarajevo Journal of Mathematics, 2022)
In this paper, we establish new double weighted results of Chebyshev inequalities involving the Riemann-Liouville fractional integral operator with respect to another measurable, increasing, positive and monotone function. In particular, some recent results are deduced as some special cases.